The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1177/15248399231221163
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraceptive Side Effects and Nonhormonal Alternatives on TikTok: A Content Analysis

Emily J. Pfender,
Kate Tsiandoulas,
Stephanie R. Morain
et al.

Abstract: The use of hormonal contraceptives is decreasing in the United States alongside a growing interest in nonhormonal contraceptive options. Social media messaging may be contributing to this trend. TikTok thus offers a novel opportunity to understand how people share information about risks and alternatives for pregnancy prevention. To describe the availability and content of information about hormonal contraceptive side effects and nonhormonal contraceptive options on TikTok, we conducted a content analysis of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Vieth et al (2021) found that the internet was the most common source of contraceptive information among German women [29]. Studies, for instance, researched the experiences of birth control on YouTube [30][31][32][33], TikTok [34,35], and Reddit [36]. An analysis of German SNSs' contraception content on You-Tube, Instagram, and TikTok found clear shortcomings in the quality and completeness of information on these sites [37].…”
Section: The Pill and Mainstream Media-a Problematic Relationship?mentioning
confidence: 99%
“…Vieth et al (2021) found that the internet was the most common source of contraceptive information among German women [29]. Studies, for instance, researched the experiences of birth control on YouTube [30][31][32][33], TikTok [34,35], and Reddit [36]. An analysis of German SNSs' contraception content on You-Tube, Instagram, and TikTok found clear shortcomings in the quality and completeness of information on these sites [37].…”
Section: The Pill and Mainstream Media-a Problematic Relationship?mentioning
confidence: 99%